Electronic Theses: Swiss Perspectives - Niederer, Ulrich; Weigel, Ulrich; Gillieron-Garber, Marie-Pierre; Böhler, Karl (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
To offer theses electronically to its users is something that has been discussed in Swiss university libraries for some time now. There are two main reasons that it has not yet been realized anywhere in Switzerland: On the one hand, the two large university library networks have had big library system migrations to cope with (first the „Réseau Romand” in the French speaking part moved to VTLS, then, in the last two years, the „Informationsverbund Deutschschweiz, IDS” in the German speaking part switched to Aleph by Ex Libris). These migrations used up all available personnel resources. On the other hand, the federalist organization of all things politic in Switzerland, including the university system, means that there are hardly any national programmes to further and finance projects on a national level (or cantonal, for that matter) - in contrast to most other European countries where such programmes have proved to be a very strong incentive for developing various aspects of the digital library.